Vigil Harbor - Glass, Julia, 1956- (Pantheon Books, 2022)
"A decade in the future, in the historic town of Vigil Harbor, there's been a rash of divorces among the yacht-club set; a marine biologist despairs at the state of the world; a spurned wife is bent on revenge; and the renowned architect Austin Kepner pursues a passion for building homes to withstand the escalating fury of coastal storms. Brecht, Austin's stepson, has dropped out of college and retreated home from New York after narrowly escaping one of the domestic terrorist acts that, like hurricanes, are becoming all too common. When two outsiders come to town--one a woman determined to solve the disappearance of a long-lost lover who links her to Austin, the other a man with subversive charms--the fates of Vigil Harbor's residents become intertwined on one remarkable day and a long-held secret involving a selkie comes to light. In a Time of Tempests reveals Julia Glass in all of her virtuosity, braiding together multiple voices and several dazzling strands of plot in a story that mingles mortal longings and fears with immortal mysteries of the deep as well as the heart"--